Does the existence of income inequality contribute to the volume of carbon dioxide emission? An analysis on selected southeast Asia countries - Fong, Daniel Weng Yew; Loh, Jason Jia Shun; Tan, Chou Hong; Tan, Sin Rou (2023)
With an increasing in carbon emission, factors in Southeast Asia’s economic development that will influence the increase in carbon emissions needs to be studied more thoroughly in order to address the issue of rising carbon emissions. This study's primary goal is to look into the factors that have influenced carbon emissions in six Southeast Asia nations from 1981 to 2020. The data used in this research is secondary data with a total number of observations of 240. For analysis, we applied panel data techniques such as pooled least squares, fixed effects, random effects. The Environmental Kuznets Curve (EKC) hypothesis is supported by our models' findings in the Southeast Asia countries, where GDP per capita and its square term have positive and negative coefficients. In this research, the result illustrates that foreign direct investment (FDI), GDP per capita, urbanization positively contribute to environmental degradation in Southeast Asia countries’ economies. This study's findings add to the body of knowledge on environmental degradation and give policymakers in Southeast Asia countries’ economies a better understanding of environmental degradation. By examining all the independent variables that this study found to be associated with an increase in carbon emissions, policymakers can think about how to manage these variables going forward in order to lower carbon emissions.